Gambaran Pelaksanaan Proses Assembling Berkas Rekam Medis Pada Pasien Rawat Inap Di Rumah Sakit X Purwodadi - Ningrum Tri Wahyuni; Wahyuni Arumsari; Dwi Nur Siti Marchamah (Indonesian Journal of Health Community, 2024)
Medical records in hospitals are a crucial aspect that reflects the quality of service, measured through the completeness of information filling. The purpose of this study was to identify the function of the assembling process, understand the implementation of the main tasks of assembling, and analyze the inhibiting factors in the assembling process at Rumah Saki X Purwodadi. Descriptive qualitative method was used in this research. Data were collected through observation, interviews, and documentation. Data processing with source triangulation involved four informants. Data analysis used the Miles and Huberman method for reduction, data presentation, and conclusion. The results showed the excellence of the medical record assembling process at Hospital X, especially in form preparation, information documentation, document control, and patient identification supervision. Challenges were found such as form filling errors and constraints in supervision, which could affect the integrity of medical records. Analyze assembling tasks such as the efficiency of re-assembling forms and the importance of careful examination of medical record data. Improvements were needed such as medical record form filling errors. Constraining factors included staff attitudes affecting service quality and low motivation due to high workload. Suggestions involve periodic training, increased staff motivation, and adoption of medical record technology.